Costume Digital Restoration of the Tomb Mural of YanFei (Journal of Fiber Bioengineering and Informatics, 2024)
Based on the image and textual data, the characteristics of the style, structure and pattern of thecostumes in the Tang tomb murals were analysed using garment engineering. The size of each part ofthe costumes was inferred using the proportion method, and a set of formulas was summarised. Basedon comparing three kinds of pattern extraction algorithms, the Canny operator combined with themorphology algorithm was optimal for pattern extraction for costume restoration. 3D virtual technologywas used to digitally restore the costumes of the tomb murals of YanFei. The effect of costume restorationwas evaluated according to the rank sum operation method and questionnaire results.
Keywords: Digital Restoration; Costume Structure; Pattern Extraction; Image Segmentation Algorithm; 3D Virtual Technology; The YanFei’s Tomb Mural Costumes.